Locotypes: An Exploration of an Alternative Signage System That Challenges the Current Approach of Prioritising Conformity in Designing and Reading of Wayfinding Signage Systems - Lam, Letitia (Auckland University of Technology, 2007)
Locotypes is a practice-based research project that is intended to suggest an alternative approach to traditional ways of designing and reading wayfinding signage systems. This is an alternative approach that will not follow the traditional universal* approach of design for effective signage application. The aim of the project is to suggest a rethinking of visual conformity as the main objective in designing a wayfinding signage system. The research question is: what are the opportunities and impediments to designing a wayfinding signage system that acknowledges and is equally influenced by the local as well as global characteristics of a particular system? This practical research project takes on a hypothesis that the approach of prioritising GLOBAL* visual conformity typical of the standard signage systems fails to reflect the mix of culturally specific and multi-cultural profiles that are peculiar to the "actual specific local"* contexts. I am intending to explore an alternative way of designing a coherent wayfinding signage system which can be read from both a LOCAL* and GLOBAL point of view. This system could potentially change the traditional notions of developing a wayfinding signage system and triggers further explorations in design industry
Keywords: Locotypes; Signage; Multi-cultural; Visual; Design; Environment; MTR System